Perancangan Basis Data Sistem Informasi Penjualan Barang (Studi Kasus: Minimarket â€œABCâ€ Sidareja) - Bambang Sumantri, R Bagus; Mahardika, Fajar (STMIK Komputama Majenang, 2020)
Data processing to produce a computerized information is a tool that needed at this time in various types of business because the information capable presented within quickly and accurately time. Information which capable of quickly and accurately presented can produce quickly and effective decision but the database design that applied in a database management system is no less important Good database design will facilitate the implementation of aplications and optimize the performance of the database manajemen system itself.